Short Plays and Drama in EFL Classrooms as Perceived by Secondary School Students: the Role and Impact - Dini Rosita Sari (Universitas Islam Negeri Walisongo Semarang, 2022)
This quantitative study investigates the role and impact of short plays and drama on English as a foreign language (EFL) students. A total of 72 students from a secondary school in North Kalimantan in Indonesia participated in the study. Data was collected through a questionnaire consisting of 8 items, which were later classified into three different focuses of inquiries; psychological, instrumental, and pedagogical aspects. The study results indicate that secondary school students viewed short play from the three perspectives positively. Findings also suggest that the application of short play in EFL classrooms must be preceded by a careful selection of literary texts and careful planning of short play instructional design. Finally, the study calls for further attempts to integrate secondary school EFL curriculum and literature, implying the needs for appropriate drama-based activity pedagogy and professional development programs.